POTENSI ANTIBAKTERI GEL EKSTRAK ETANOL DAUN PARE (Momordica charantia L) TERHADAP BAKTERI Staphylococcus aureus ATCC 25923 - Afrida Tri Ningsih; Novena Yety Lindawati; Aulia Nur Rahmawati (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Bacteria The main causes of skin infections among them caused by staphylococcus aureus bacteria, each infected network usually appears typical signs such as inflammation and abscess formation. Pare leaves (Momordica Charantia L.) can be used as antibacterial because they contain flavonoids, alkaloids, saponins, and tannins. This study aims to obtain a gel preparation of the pare leaf ethanol extract that has antibacterial activity against Staphylococcus aureus. Dietary leaf extract pare is done by Maceration method using 70% ethanol solvent. Deads are made with a concentration of 15%, 20% and 25%. The quality control test of the gel preparations include tests for homogeneity, organoleptic, dispersibility, adhesion, pH, viscosity and irritation then continued with antibacterial activity tests. The results showed that formula 3 (concentration 25%) met the requirements of the physical properties test including organoleptic test of green color, brownish concentrated, transparent, distinctive aroma, thick texture, homogeneous, has a pH of 5.8±0.0, viscosity 3100±0.0 cps, spreadability 5.3 ±0.27 cm, adhesion 1.22±0.02 seconds, and does not irritate the skin and has the greatest antibacterial activity. The antibacterial activity test showed that the diameter of the inhibition zones obtained in the ethanol extract gel preparations of pare leaves at concentrations of 15%, 20% and 25% were 16.58±0.33 mm, 17.87±0.78 mm, and 22.20±0.78 mm, respectively.